Recently discovered materials for writing the history of christian Nubia - Frend, W. H. C. (Studies in church history, 1975)
Chance discoveries have been among the ‘uncovenanted blessings’ that have fallen to the study of new testament times and the early church. The finding of the Isaiah scroll by a shepherd boy in the judaean desert in 1947 led to the greatest discovery in biblical studies of all time, that of the Dead Sea scrolls and the essene monastery of Kharbet Q’mran. Similarly, the recovery of the gnostic library of 48 separate books from a Christian cemetery at Nag-Hammadi, not far from Luxor, in 1946, has thrown a wholly unexpected light on the complex of beliefs and attitudes of orthodox Christianity’s great rival during the second and early third centuries, gnosticism. Recently, professor Morton Smith has made the boldest claims on behalf of a ‘secret Gospel of Mark’ used apparently in Alexandria in the second century AD. An extract from this gospel he found in the library of the monastery of Mar Saba near Jerusalem, quoted in a letter which may be attributed correctly to Clement of Alexandria circa 190 AD.